Main marketing trends in the Russian cinema market in the current realities - O. V. Zhuravleva; A. S. Lobacheva (Вестник университета)
The article examines current marketing trends in Russian cinema and film industry, which have emerged in the 21st century in Russian cinema and international federation of film societies. The aim of the study is to define the directions of marketing strategies for enlarging the target audience and extracting the maximum possible profit from cinematographic business. Based on key works on marketing and their own observations, the authors investigated the concept and essence of marketing, its content and specifics. Various ways of increasing the audience of cinemas and customer loyalty programmes were analysed. The main societal trends, which influence the creation of cinematographic images in contemporary cinematography, were identified, and the factors of modern society development and their correlation with the world of cinematography, including the degree of their influence, were pointed out. The results of the study can serve as a basis for evaluating the effectiveness of marketing strategies.